2022
DOI: 10.3390/pharmaceutics15010102
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac Loaded Biodegradable Nanoparticles as Antitumoral and Antiangiogenic Therapy

Abstract: Cancer is identified as one of the main causes of death worldwide, and an effective treatment that can reduce/eliminate serious adverse effects is still an unmet medical need. Diclofenac, a non-steroidal anti-inflammatory drug (NSAID), has demonstrated promising antitumoral properties. However, the prolonged use of this NSAID poses several adverse effects. These can be overcome by the use of suitable delivery systems that are able to provide a controlled delivery of the payload. In this study, Diclofenac was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…These values may be explained by an initial rapid release caused by the free Ca(OH) 2 located in the outer part of the NPs causing that K d value. Once the free Ca(OH) 2 is released, the release of Ca(OH) 2 from the inside of the NPs starts, allowing a prolonged and slow profile until the maximum release is reached (Esteruelas et al., 2023). Conversely, Ca(OH) 2 ‐NPs‐gel best fit was the Korsmeyer‐Peppas equation.…”
Section: Resultsmentioning
confidence: 99%
“…These values may be explained by an initial rapid release caused by the free Ca(OH) 2 located in the outer part of the NPs causing that K d value. Once the free Ca(OH) 2 is released, the release of Ca(OH) 2 from the inside of the NPs starts, allowing a prolonged and slow profile until the maximum release is reached (Esteruelas et al., 2023). Conversely, Ca(OH) 2 ‐NPs‐gel best fit was the Korsmeyer‐Peppas equation.…”
Section: Resultsmentioning
confidence: 99%
“…The dissociation constant (K d ) of APG-NLC was higher in both the slow and fast phases than in free APG (0.07 and 0.27 vs 0.02 h), thus indicating a prolonged release. 37 Moreover, the half-life results (t 1/2 ) showed that there was a burst release at the beginning during the fast phase of the formulation, but during the slow phase, it had a sustained release, with a t 1/2 value of 160.5 h. 50…”
Section: Biopharmaceutical Behaviourmentioning
confidence: 98%
“…To determine the antiangiogenic effects of APG-NLC, a modified chorioallantoic membrane (CAM) test was used. 37 It was carried out using fertilised chicken eggs incubated at 37 °C and 85 % humidity. A lateral window was opened on the eggshell on the third day of incubation, and after 24 h of stabilization, 40 µL of the sample were inoculated to the CAM.…”
Section: Antiangiogenic Capacitymentioning
confidence: 99%
“…Because the mechanism of the anti-inflammatory action of diclofenac and GCs is due to COX-2 and NF-kB inhibition, this could be one of the reasons for their cytotoxic effect on cancerous cells. Diclofenac has also antiangiogenic activity [ 25 ]. Similarly, glucocorticoids have both anti-inflammatory and antitumor activities [ 17 ].…”
Section: Introductionmentioning
confidence: 99%